"They're the modern-day gay bar": Exploring the uses and gratifications of social networks for men who have sex with men. (October 2015) - Miller, Brandon
Highlights: Men view social networks for men who have sex with men (MSM) as safe spaces. The notion of gaydar becomes obsolete in these online contexts. These networks provide control over interactions and over the sharing of information. They are especially useful for men with barriers to accessing queer offline space. They are being used for a variety of aims, including sex, friendship, and romance. Abstract: There currently exist many mobile social networks for men who have sex with men (MSM), from stand-alone applications like Grindr and Jack'd, to the on-the-go versions of established websites such as Adam4Adam or Manhunt. It has become increasingly common for MSM to seek out others by means of online social networks, and for a variety of purposes. This paper explores the motivations for MSM-specific social networking use, and the sought gratifications associated with this type of computer-mediated interpersonal interaction. In an online survey yielding 143 participants, men were asked their thoughts about social networking phone applications for gay, bisexual, and other MSM. Using these data, seven categories of sought gratifications were identified: safety, control, easiness, accessibility, mobility, connectivity, and versatility.